ANALISIS PROGRAM PNPM MANDIRI PEDESAAN TERHADAP KESEJAHTERAAN MASYARAKAT DI DESA KARKITAN BAYAT KLATEN KESEJAHTERAAN MASYARAKAANALISIS PROGRAM PNPM MANDIRI PEDESAAN TERHADAP KESEJAHTERAAN MASYARAKAT DI DESA KARKITAN BAYAT KLATEN - Jima Jima (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2013)
Povertyis a classic problemthat has been happening in Indonesia.National Community Empowerment Program(PNPM) is one of thegovernmentprogramsundertakenin an effort tocontrolit.The purposeof this studywas to determine therole ofhuman resource managementin the success ofthe NationalProgramfor Community Empowerment (PNPM) in the village of Krakitan,Bayat, Klaten. This research is aqualitative descriptive research type (explanatory), while thesampletaken by purposive sampling the sampleintentionally predetermined based on the considerationin accordancewith the intentandpurpose of the studycomprised of stakeholders who knowthe problem sand conditions Krakitan village, Bayat, Klaten.The data was collectedby observation, Interview Guide or key person, where asthe method usedis AHP (Analytic Hierarchy Process). The results ofthe analysis found thatamong manajemnroleof human resourcesisthe most power ful planning (planning) with the eigen vector for 0444 means that44% of the program’ssuccess PNPM Rural Krakitan village, Bayat, Klaten played by planning.